2015
DOI: 10.1075/dujal.4.1.07jin
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with foreign language anxiety

Abstract: This paper reports a study that investigates and compares the effects of foreign language proficiency, social status of a learner's family, self-esteem, and competitiveness on FL anxiety. Chinese university students (N = 146), who were learning Japanese and English, participated in this study. Social status data were collected once with the Social Status Scale. Other variables were measured twice over a two-month interval, using the Competitiveness Index, the Self-esteem Scale, the English/Japanese Classroom A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
3
8
2
Order By: Relevance
“…As a result of this, it could be claimed that the level of FLL anxiety students experienced while learning a foreign language was not influenced by the financial status of their families. This finding is in line with the findings of the research literature (e.g., Jin, de Bot, and Keijzer, 2015;Wilson, 2006), which revealed that monthly income of families did not have a significant impact on students' FLL anxiety. In other words, students' FLL anxiety does not change according to monthly income of families, meaning that families with high or low monthly income do not have a significant impact on the level of FLL anxiety their children experience in the classroom.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a result of this, it could be claimed that the level of FLL anxiety students experienced while learning a foreign language was not influenced by the financial status of their families. This finding is in line with the findings of the research literature (e.g., Jin, de Bot, and Keijzer, 2015;Wilson, 2006), which revealed that monthly income of families did not have a significant impact on students' FLL anxiety. In other words, students' FLL anxiety does not change according to monthly income of families, meaning that families with high or low monthly income do not have a significant impact on the level of FLL anxiety their children experience in the classroom.…”
Section: Discussionsupporting
confidence: 91%
“…The research literature also reported that there was not a statistical significance among students in terms of their FLL anxiety according to father's education status (e.g., Awan et. al., 2010;Jin, de Bot, & Keijzer, 2015;Öner & Gedikoğlu, 2007), which confirmed the current finding of the research. According to Iwaniec (2016), parents' role is very important in language learning motivation of their children.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, researchers have also investigated the effect of competitiveness on FL anxiety. However, it remains unclear whether it is a positive predictor, a negative predictor, or a non-significant predictor of FL anxiety levels (Jin et al, 2015a;Onwuegbuzie et al, 1999;Toth, 2007). Another lower-rank personality trait that has been related to FL anxiety is trait emotional intelligence (Trait EI), or trait emotional self-efficacy if its self-evaluative nature is stressed (Dewaele, Petrides, & Furnham, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The research questions were drawn from empirical studies (Lin, 2003;Tyan and Shen, 2003;Jin et al, 2015) and integrated from Sociocultural Theory and Input Hypothesis. In Sociocultural Theory, learners are taken as active agents in the learning process, different from the roles learners play in a traditional teacher-dominated classroom.…”
Section: Research Questionsmentioning
confidence: 99%